PENGARUH PEMBERIAN EKSTRAK TAUGE DAN BAWANG MERAH PADA PERTUMBUHAN BIBIT GAHARU (Aquilaria Malaccensis) - fenty dwi jayanti; Duryat Duryat; afif bintoro (Jurnal Belantara, 2019)
Agarwood is a plant that has high economic value and its demand continues to increase from time to time, therefore it is necessary to provide a natural hormones to help the growth of agarwood seedlings to have good quality and quantity.  The purpose of  study ware to determine the effect of extract  bean sprouts application and onion extract application to increase the growth of A.malaccensis seedlings and to find out the best dosage of bean sprout extract and  onion extract to increase the seedling growth.  The study was designed in  a complete randomized design (CRD) in 9 treatments namely control,  bean sprout extract at the dose of 100 g/l, 200 g/l, 300 g/l, 400 g/l and onion extract at the dose of 100 g/l, 200 g/l, 300 g/l, and 400 g/l.  The homogeneity test, analysis of variance and LSD test were employed as the data analysis. The results of study showed that bean sprouts and  onion extract application, have a significant effect to the increasing of height (up to 11,47 cm on the treatment onion extract at a dose of 200 g/l), number of leaves (up to 9,67 leaves on the treatment  onion extract at a dose of 200 g/l), and seedling quality index (up to 0,18 on the treatment onion extract at a dose of 200 g/l).  The best treatment to the increase of A.malaccensis seedlings was the onion extract application at a dose of 200 g/l. The treatment can be applied in agarwood seeds to get maximum results.